It Is About Believing: Superstition and Religiosity - Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2003)
This paper has a novel framework analysing what shapes superstition in a multivariate analysis. The results indicate that socio-demographic and socio-economic variables matter. The results also indicate that there is a certain concurrence between churches and superstitious beliefs. In most of the cases we observe a negative correlation between superstition and attendance of church and other religious activities. Closeness to the churches goes in line with lower superstition. On the other hand, a generally higher perceived religiosity increases superstition. Furthermore, there is the tendency that people without a religious denomination have the lowest belief in superstition. Finally, the results indicate that there is a strong variety in superstition among countries. Especially people from formerly Communist countries have a higher degree of superstition than others.
Keywords: K42; 330; Superstition; Religiosity; Culture